Degradation of huntingtin mediated by a hybrid molecule composed of IAP antagonist linked to phenyldiazenyl benzothiazole derivative. Issue 4 (15th February 2018) - Tomoshige, Shusuke; Nomura, Sayaka; Ohgane, Kenji; Hashimoto, Yuichi; Ishikawa, Minoru
Graphical abstract: Abstract: Huntington's disease (HD) is an autosomal dominant neurodegenerative disorder caused by aggregation of mutant huntingtin (mHtt), and removal of mHtt is expected as a potential therapeutic option. We previously reported protein knockdown of Htt by using hybrid small molecules (Htt degraders) consisting of BE04, a ligand of ubiquitin ligase (E3), linked to probes for protein aggregates. Here, in order to examine the effect of changing the ligand, we synthesized a similar Htt degrader utilizing MV1, an antagonist of the inhibitor of apoptosis protein (IAP) family (a subgroup of ubiquitin E3 ligases), which is expected to have a higher affinity and specificity for IAP, as compared with BE04. The MV1-based hybrid successfully induced interaction between Htt aggregates and IAP, and reduced mHtt levels in living cells. Its mode of action was confirmed to be the same as that of the BE04-based hybrid. However, although the affinity of MV1 for IAP is greater than that of BE04, the efficacy of Htt degradation by the MV1-based molecule was lower, suggesting that linker length between the ligand and probe might be an important determinant of efficacy.